ANALYSIS OF LAVENDER AROMATHERAPY APPLICATION TO REDUCE BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A CASE STUDY - Sapeni, Muhammad Al-Amin R.; asriana, Hasriana; Anwar, Irawati; Yunus, Suwardha; Iwan, Iwan; Taniguch, Toshiyo; Lillehei, Angela Smith (An Idea Health Journal, 2025)
Introduction: Hypertension is defined as a condition in which an individual has a systolic blood pressure ? 140 mmHg and a diastolic blood pressure ? 90 mmHg. Systolic blood pressure is the main measure used to diagnose hypertension. Hypertension is often referred to as a "silent killer" due to its asymptomatic nature, causing patients to be unaware of their condition. Globally, 1.28 billion people are affected by hypertension; in Indonesia, 70 million people (28%) have hypertension, with Jakarta ranking 9th among Indonesian provinces in 2017 with a prevalence of 33.43%. Methods: This study employed a descriptive narrative case study design. The subjects were three adult patients diagnosed with hypertension. Results: The case study showed a non-pharmacological effect of lavender aromatherapy in lowering blood pressure among hypertensive patients. All three patients were given lavender aromatherapy over three days. The goal was to reduce pain and stabilize blood pressure. Expected outcomes included decreased pain complaints, improved vital signs, and reduced BP. Conclusion: This study suggests that lavender aromatherapy can serve as an alternative nursing intervention for reducing blood pressure in hypertensive patients and can be independently administered by nurses as a non-pharmacological therapy.